Eligibility recertification and dynamic opt-in incentives in income-tested social programs: Evidence from Medicaid/CHIP - Zhuan Pei (W.E. Upjohn Institute for Employment Research, 2015)
Conventional labor supply studies assume constant eligibility monitoring of income-tested program participants, but this is not true for most programs. For example, states can allow children to enroll in Medicaid/CHIP for 12 months regardless of family income changes. A long recertification period reduces monitoring costs but is predicted to induce program participation by temporary income adjustments. However, I find little evidence of strategic behavior from the 2001 and 2004 Survey of Income and Program Participation. Given the lack of dynamic responses, I propose a framework to compute the optimal recertification period and find 12 months to be its lower bound.
Keywords: I38; J20; 330; Labor Supply; Medicaid; CHIP; Continuous Eligibility; Recertification